2000
DOI: 10.1152/jn.2000.83.4.2071
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A Mediates the Modulation of the Slow Ca2+-Dependent K+Current,IsAHP, by the Neuropeptides CRF, VIP, and CGRP in Hippocampal Pyramidal Neurons

Abstract: We have studied modulation of the slow Ca(2+)-activated K(+) current (I(sAHP)) in CA1 hippocampal pyramidal neurons by three peptide transmitters: corticotropin releasing factor (CRF, also called corticotropin releasing hormone, CRH), vasoactive intestinal peptide (VIP), and calcitonin gene-related peptide (CGRP). These peptides are known to be expressed in interneurons. Using whole cell voltage clamp in hippocampal slices from young rats, in the presence of tetrodotoxin (TTX, 0.5 microM) and tetraethylammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
97
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 105 publications
6
97
1
Order By: Relevance
“…CRF receptors are G protein-coupled, and their stimulation results in activation of adenylate cyclase and protein kinase A (28,29). It is possible that these signaling pathways link acute stress to increases in neuronal activity and A␤ levels.…”
Section: Discussionmentioning
confidence: 99%
“…CRF receptors are G protein-coupled, and their stimulation results in activation of adenylate cyclase and protein kinase A (28,29). It is possible that these signaling pathways link acute stress to increases in neuronal activity and A␤ levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cellular cAMP levels (58,59), promoting phosphorylation of cAMP-response element-binding protein transcription factor (41,60,61) is an attractive possibility, because cAMP-response element-binding protein is selectively activated in developing hippocampal neurons (62) and is involved in dendritic differentiation (63). The selective effects of CRF on proximal dendrites may be dictated by the selective distribution of CRF 1 at this age (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the suppression of sAHP in CA1 pyramidal neurons appears to be mainly mediated by the level of the second messenger cAMP and the candidate kinase for synaptic tagging PKA (Haug and Storm, 2000;Storm, 1993, 1995). Furthermore, recent evidence suggests that CREB activity, which is known to be downstream of such inputs (Berke and Hyman, 2000), might mediate sustained changes in intrinsic excitability (Dong et al, 2006;Han et al, 2006;Lopez de Armentia et al, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is well known that DG granular neurons have a prominent sAHP and that this current is block by adrenergic and dopaminergic activation. Several studies have also showed that the reduction of the AHP facilitates synaptic plasticity phenomena (Cohen et al, 1999;Fuenzalida et al, 2007;Haug and Storm, 2000;Sah and Bekkers, 1996). Therefore, a reduction of the sAHP produced by β-adrenergic metabotropic receptors in granular neurons can reduce the threshold required to achieve L-LTP in glutamatergic inputs and contribute to behavioral LTP-reinforcement.…”
Section: Accepted Manuscriptmentioning
confidence: 99%